Efficient third harmonic generation from FAPbBr3 perovskite nanocrystals. Issue 45 (13th November 2020) - Rubino, Andrea; Huq, Tahiyat; Dranczewski, Jakub; Lozano, Gabriel; Calvo, Mauricio E.; Vezzoli, Stefano; Míguez, Hernán; Sapienza, Riccardo
Abstract : Experimental evidence and characterization of nonlinear third harmonic generation from hybrid FAPbBr3 perovskite nanocrystals embedded in a porous thin film demonstrate a new potential application of these semiconductors. Abstract : The development of versatile nanostructured materials with enhanced nonlinear optical properties is relevant for integrated and energy efficient photonics. In this work, we report third harmonic generation from organic lead halide perovskite nanocrystals, and more specifically from formamidinium lead bromide nanocrystals, ncFAPbBr3, dispersed in an optically transparent silica film. Efficient third order conversion is attained for excitation in a wide spectral range in the near infrared (1425 nm to 1650 nm). The maximum absolute value of the modulus of the third order nonlinear susceptibility of ncFAPbBr3, χ (3)NC, is derived from modelling both the linear and nonlinear behaviour of the film and is found to be χ (3)NC = 1.46 × 10 −19 m 2 V −2 (or 1.04 × 10 −11 esu) at 1560 nm excitation wavelength, which is of the same order as the highest previously reported for purely inorganic lead halide perovskite nanocrystals (3.78 × 10 −11 esu for ncCsPbBr3 ). Comparison with the experimentally determined optical constants demonstrates that maximum nonlinear conversion is attained at the excitonic resonance of the perovskite nanocrystals where the electron density of states is largest. The ease of synthesis, the robustness and the stability provided by the matrix make this material platform attractive for integrated nonlinear devices.